Research of the fine structure of the radio galaxy 3C 234 with radio interferometer URAN-2 - Vashchishin, R.V.; Megn, A.V.; Rashkovsky, S.L.; Shepelev, V.A.; Inyutin, G.A.; Brazhenko, A.I.; Bulatsen, V.G. (Кинематика и физика небесных тел, 2005)
The brief description and the basic characteristics of the radio interferometer URAN-2 aerial system, included in VLBI decameter system URAN, are presented. The research results of the 3C 234 angular structure with URAN system are submitted. The model of radiobrightness distribution of this source at frequencies of 20 and 25 MHz is obtained. With the URAN-2 radio interferometer compact details in a radio galaxy have been found and their contribution to the general flow of a radio emission at decameter waves is determined. The effect of reabsorption in compact details (hot spots) is found and their true angular size are determined based on the research of the 3C234 spectrum.